(untitled) (Revista de História Regional, 2007)
The participation of the province of Minas Gerais in the Independence of Brazil has been seen by the historiography in the form of an immediate adhesion to Pedrino project, for the importance of Mines in the context of the Center-South, as originary element of the form acquired for the separatist process. In fact, the integration of Mines in the Pedrino project was not instantaneous and implied the shock between trends absolutists, autonomists - perhaps republican - and the rising interest in the leadership of prince D. Pedro. Moreover, it understood the construction of a social contract that mobilized the mining villages, and in special its city councils, different degrees of understanding of the relation between the monarchic authority and the representation of the society.